First year of energetic particle measurements in the inner heliosphere with Solar Orbiter's Energetic Particle Detector - Wimmer-Schweingruber RF; Janitzek NP; Pacheco D; Cernuda I; Lara FE; Gomez-Herrero R; Mason GM; Allen RC; Xu ZG; Carcaboso F; Kollhoff A; Kuhl P; et al. (EDP SCIENCES S A, 2022)
Context. Solar Orbiter strives to unveil how the Sun controls and shapes the heliosphere and fills it with energetic particle radiation. To this end, its Energetic Particle Detector (EPD) has now been in operation, providing excellent data, for just over a year.
Aims. EPD measures suprathermal and energetic particles in the energy range from a few keV up to (near-) relativistic energies (few MeV for electrons and about 500 MeV nuc(-1) for ions). We present an overview of the initial results from the first year of operations and we provide a first assessment of issues and limitations. In addition, we present areas where EPD excels and provides opportunities for significant scientific progress in understanding how our Sun shapes the heliosphere.
Methods. We used the solar particle events observed by Solar Orbiter on 21 July and between 10 and 11 December 2020 to discuss the capabilities, along with updates and open issues related to EPD on Solar Orbiter. We also give some words of caution and caveats related to the use of EPD-derived data.
Results. During this first year of operations of the Solar Orbiter mission, EPD has recorded several particle events at distances between 0.5 and 1 au from the Sun. We present dynamic and time-averaged energy spectra for ions that were measured with a combination of all four EPD sensors, namely: the SupraThermal Electron and Proton sensor (STEP), the Electron Proton Telescope (EPT), the Suprathermal Ion Spectrograph (SIS), and the High-Energy Telescope (HET) as well as the associated energy spectra for electrons measured with STEP and EPT. We illustrate the capabilities of the EPD suite using the 10 and 11 December 2020 solar particle event. This event showed an enrichment of heavy ions as well as He-3, for which we also present dynamic spectra measured with SIS. The high anisotropy of electrons at the onset of the event and its temporal evolution is also shown using data from these sensors. We discuss the ongoing in-flight calibration and a few open instrumental issues using data from the 21 July and the 10 and 11 December 2020 events and give guidelines and examples for the usage of the EPD data. We explain how spacecraft operations may affect EPD data and we present a list of such time periods in the appendix. A list of the most significant particle enhancements as observed by EPT during this first year is also provided.